DIGITAL TRANSFORMATION IN SUPPLY CHAIN MANAGEMENT: THE IMPACT OF BLOCKCHAIN TECHNOLOGY IMPLEMENTATION ON OPERATIONAL EFFICIENCY - Fauziah, Luluk; Mashudi, (Branding: Jurnal Manajemen dan Bisnis, 2024)
Digital transformation in supply chain management has encouraged companies to adopt innovative technologies to improve efficiency and competitiveness. One technology that is increasingly being implemented is blockchain, which offers transparency, security, and automation in supply chain management. However, the integration of blockchain with existing systems still faces various challenges, including technical barriers, workforce readiness, and the need for clearer regulations. This study aims to analyze the impact of blockchain technology implementation on operational efficiency in supply chain management. The research method used is a qualitative approach with literature analysis from various relevant sources. The data obtained will be systematically reviewed to identify patterns, challenges, and potential for blockchain technology development in the supply chain. The results of the study show that blockchain can improve product traceability, speed up transactions, and reduce operational costs in the supply chain. The implementation of this technology also has the potential to change the competitive landscape of the industry by creating a more efficient and transparent system. Therefore, an appropriate integration strategy and regulatory support are needed to ensure wider and more sustainable blockchain adoption.